State-of-the-Art Review of the Applicability and Challenges of Microbial-Induced Calcite Precipitation (MICP) and Enzyme-Induced Calcite Precipitation (EICP) Techniques for Geotechnical and Geoenvironmental Applications - Almajed, Abdullah; Lateef, Mohammed Abdul; Moghal, Arif Ali Baig; Lemboye, Kehinde (Crystals (Basel), 2021)
The development of alternatives to soil stabilization through mechanical and chemical stabilization has paved the way for the development of biostabilization methods. Since its development, researchers have used different bacteria species for soil treatment. Soil treatment through bioremediation techniques has been used to understand its effect on strength parameters and contaminant remediation. Using a living organism for binding the soil grains to make the soil mass dense and durable is the basic idea of soil biotreatment. Bacteria and enzymes are commonly utilized in biostabilization, which is a common method to encourage ureolysis, leading to calcite precipitation in the soil mass. Microbial-induced calcite precipitation (MICP) and enzyme-induced calcite precipitation (EICP) techniques are emerging trends in soil stabilization. Unlike conventional methods, these techniques are environmentally friendly and sustainable. This review determines the challenges, applicability, advantages, and disadvantages of MICP and EICP in soil treatment and their role in the improvement of the geotechnical and geoenvironmental properties of soil. It further elaborates on their probable mechanism in improving the soil properties in the natural and lab environments. Moreover, it looks into the effectiveness of biostabilization as a remediation of soil contamination. This review intends to present a hands-on adoptable treatment method for in situ implementation depending on specific site conditions.